2007
DOI: 10.1016/j.jalgebra.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian properties of total rings of quotients

Abstract: In this paper we consider five possible extensions of the Prufer domain notion to the case of commutative rings with zero divisors and relate the corresponding properties on a ring with the property of its total ring of quotients. We show that a Prufer ring R satisfies one of the five conditions if and only if the total ring of quotients Q(R) of R satisfies that same condition. We focus in particular on the Gaussian property of a ring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 12 publications
1
114
0
Order By: Relevance
“…Glaz [30] showed that (1) implies (5) while Lucas [42] showed the reverse implication (5) implies (1). Bazzoni and Glaz [7] proved the equivalence of (1) and (4). In addition, Tsang showed that the prime ideals in a local Gaussian ring are totally ordered.…”
Section: Theorem 36 ([2351]) Let R Be An Integral Domain Then R Ismentioning
confidence: 91%
See 2 more Smart Citations
“…Glaz [30] showed that (1) implies (5) while Lucas [42] showed the reverse implication (5) implies (1). Bazzoni and Glaz [7] proved the equivalence of (1) and (4). In addition, Tsang showed that the prime ideals in a local Gaussian ring are totally ordered.…”
Section: Theorem 36 ([2351]) Let R Be An Integral Domain Then R Ismentioning
confidence: 91%
“…The first approach, taken by Glaz in [30] utilizes conditions which control zero divisors. The second approach, taken by Bazzoni and Glaz in [7] and by Boynton in [10], consists of imposing conditions on Q(R). We describe the former approach first, starting with a brief background on zero divisor controlling conditions.…”
Section: Conditions That Allow Reversal Of Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many rings that are not domain, but still Gaussian. For more on Gaussian rings, one may refer to [1], [4], [2], and [6]. In the next section, we will define Gaussian algebras and discuss them.…”
Section: Introductionmentioning
confidence: 99%
“…• R contains a prime ideal L such that L R L is non-zero and T-nilpotent (a slight generalization of [2,Theorem 6.4] using [1, Theorems P and 6.3]).…”
mentioning
confidence: 99%